The Contribution of Self Esteem and Family Social Support to the Women Victims of Domestic Violence Resilience - Atih Asfami; Marjohan Marjohan; Herman Nirwana (Jurnal Aplikasi IPTEK Indonesia, 2020)
The goal of this study is to examine self-esteem, family social support and resilience of victims of domestic violence at the Woment Crisis Center in Padang. Factors that affect resilience are self-esteem and family social support. This thesis utilizes a quantitative descriptive correlational technique. At the Woment Crisis Center Padang Conscience Institution, the population of this study were 77 victims of domestic violence, selected by purposeful sampling technique. The findings of this study show that self-esteem and family social support together are 23.8% important for resilience. The implications of the findings of the study can be used as an analysis of the needs of Guidance and Therapy programs and as a basis for programming.